HUBUNGAN PELAKSANAAN PEMBELAJARAN MENGGUNAKAN MEDIA ZOOM MEETING DENGAN PRESTASI BELAJAR MAHASISWA PADA MASA PANDEMI COVID-19 - Widia Wati Hutabarat; Ignatius Bondan Suratno (Jurnal Pendidikan Ekonomi dan Akuntansi, 2022)
This study aimed to determine the correlation between: 1) the use of Zoom Meetings and students’ learning achievement during the Covid-19 pandemic; and 2) complete zoom meeting facilities and students’ learning achievements during the Covid-19 pandemic. This research was a quantitative study that was conducted in May-June 2021. The population in this study were students of the Economic Education Study Program specializing in Accounting Education, Sanata Dharma University Yogyakarta, Batch of 2017-2019. The samples in the study were 105 students taken by purposive sampling technique. The research data were collected using questionnaires distributed through Google form and tested using Spearman’s rank correlation. The test results showed that: 1) there was no correlation between the use of zoom meetings and students’ learning achievements during the Covid-19 pandemic as indicated by the correlation coefficient value of -0.142 and the probability of sig.(2-tailed) = 0.149; and 2) there was no correlation between the completeness of the Zoom Meetings facilities and students’ learning achievement during the Covid-19 pandemic as indicated by the correlation coefficient value of -0.140 and the probability of sig.(2-tailed) = 0.154.Keywords: Learning implementation, Zoom Meeting media, and students’ achievements.